Barriers and enablers to monitoring and deprescribing opioid analgesics for chronic non-cancer pain: a systematic review with qualitative evidence synthesis using the Theoretical Domains Framework. Issue 5 (21st January 2022) - Cross, Amanda J; Buchbinder, Rachelle; Mathieson, Stephanie; Bourne, Allison; Maher, Christopher G; Lin, Chung-Wei Christine; O'Connor, Denise A
Abstract : Background: Understanding barriers and enablers to monitoring and deprescribing opioids will enable the development of tailored interventions to improve both practices. Objective: To perform a qualitative evidence synthesis of the barriers and enablers to monitoring ongoing appropriateness and deprescribing of opioids for chronic non-cancer pain (CNCP) and to map the findings to the Theoretical Domains Framework (TDF). Methods: We included English-language qualitative studies that explored healthcare professional (HCP), patient, carer and the general public's perceptions regarding monitoring and deprescribing opioids for CNCP. We searched MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Allied and Complementary Medicine Database (AMED) and PsycINFO from inception to August 2020. Two authors independently selected the studies, extracted the data, assessed the methodological quality using the Critical Appraisal Skills Programme, and assessed the confidence in the findings using GRADE CERQual (Grading of Recommendations Assessment, Development, and Evaluation Confidence in the Evidence from Reviews of Qualitative Research). We used an inductive approach to synthesis of qualitative data and mapped identified themes to TDF domains. Results: From 6948 records identified we included 21 studies, involving 209 HCPs and 330 patients. No studies involved carers or the general public. Five barrier themes were identified: limited alternatives to opioids, management of pain is top priority, patient understanding, expectations and experiences, prescriber pressures, and reluctance to change. Four enabler themes were identified: negative effects of opioids and benefits of deprescribing, clear communication and expectations for deprescribing, support for patients, and support for prescribers. 16 barrier and 12 enabler subthemes were identified; most were graded as high (n=15) or moderate (n=9) confidence. The TDF domains 'beliefs about consequences', 'environmental context and resources', 'social influences' and 'emotion' were salient for patients and HCPs. The domains 'skills' and 'beliefs about capabilities' were more salient for HCPs. Conclusion: Future implementation interventions aimed at monitoring and deprescribing opioids should target the patient and HCP barriers and enablers identified in this synthesis. PROSPERO registration number: CRD42019140784.